Against theoretical eclecticism and in support of a unified conceptual framework for autism intervention research - McNally, Sinéad (Trinity College (Dublin, Ireland). School of Psychology, 2009)
This thesis aims to highlight and address two key issues in autism intervention research: (1) the role of theory in autism intervention research; and (2) the practice of theoretical eclecticism in autism intervention and intervention research. It is argued that while both of these issues are critical concerns for autism intervention research, they are currently widely neglected in the research literature and need to be actively addressed by interventionist researchers and practitioners.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin